2007
DOI: 10.1177/00343552070500040501
|View full text |Cite
|
Sign up to set email alerts
|

Vocational Rehabilitation Outcomes

Abstract: This study examined the relationship between attaining a job congruent with the Individualized Plan for Employment (IPE) vocational rehabilitation goal and vocational rehabilitation outcomes. Study participants were 171 vocational rehabilitation clients served by the Maryland State Department of Education Division of Rehabilitation Services (DORS) who were successfully rehabilitated and closed (Status 26) in 2002. Results generally supported the relationship between Holland's person—environment congruence cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Future research investigating feasibility of career development services for individuals with psychiatric disorders would benefit from collecting data to explain the lack of engagement in services. In addition, while previous research has found that matching one's employment to their preferences, interests, and skills is related to increased vocational functioning (Beveridge & Fabian, 2007;Kukla & Bond, 2012;Strickler et al, 2009), this study provides no outcome information about how career development services have impacted consumers' ability to find, secure, or progress toward employment aligned with his or her preferences and talents. Future research should track consumers' progression through career development services and beyond to evaluate and monitor the impact these services have on important vocational behaviors, outcomes, and functioning.…”
Section: Limitations and Future Directionsmentioning
confidence: 82%
See 1 more Smart Citation
“…Future research investigating feasibility of career development services for individuals with psychiatric disorders would benefit from collecting data to explain the lack of engagement in services. In addition, while previous research has found that matching one's employment to their preferences, interests, and skills is related to increased vocational functioning (Beveridge & Fabian, 2007;Kukla & Bond, 2012;Strickler et al, 2009), this study provides no outcome information about how career development services have impacted consumers' ability to find, secure, or progress toward employment aligned with his or her preferences and talents. Future research should track consumers' progression through career development services and beyond to evaluate and monitor the impact these services have on important vocational behaviors, outcomes, and functioning.…”
Section: Limitations and Future Directionsmentioning
confidence: 82%
“…Similarly, Kukla and Bond (2012) found that individuals with serious mental illness who worked in jobs that matched their interests and were considered enjoyable, and that captured their attention, had significantly longer job tenure than individuals working in jobs that did not match individual interests and preferences. Moreover, Beveridge and Fabian (2007) found that consumers of state-funded vocational rehabilitation programs who obtained jobs that matched their vocational preferences had significantly higher wages than individuals who found jobs that did not match their preferences. Taken together, these findings support the message of prominent vocational rehabilitation scholars who have called attention to the need for research and practice addressing the ongoing career development of persons living with psychiatric illness (Drake & Bond, 2008;Mueser & Cook, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…JM represents a key process in these VR services that strives for an optimal fit between PwD and their target jobs (Homa, 2007). Generally, the process starts with a comprehensive assessment of the client’s work-related attributes and capabilities as the basis for determining a suitable target job (Beveridge, 2004). Subsequently, the VR professionals select appropriate interventions to align the client’s work-related skills and needs with the demands of the target job and the specific characteristics of the intended workplace.…”
Section: Introductionmentioning
confidence: 99%